Mouse Hepatocellular Carcinoma Sensitivity to Cisplatin and Docetaxel and Analysis of Related Proteins - Aymen Radhi Habeeb1, Baydaa Hussein Mutlak1 , Ahmed Majeed Al-Shammari2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Hepatocellular carcinoma (HCC) globally ranked fifth common cancer and the third-leading cause of death. This study aimed to characterize the new mouse hepatocellular carcinoma cell line (HCAM) for some of the most important proteins involved in cell cycle regulation P53, HER2/neu, and EGFR by immunocytochemistry. Also, to measure the sensitivity of the cells to some common chemotherapeutic agents such as cisplatin and docetaxel by the MTT cell viability assay. The findings of immunocytochemistry appeared that HCAM cells proven to express the p53 and EGFR positively when compared with the negative control. Furthermore, showing nuclear only low expression for the HER2/neu. For evaluation of the chemotherapeutic agent’s efficiency, the cells of hepatocellular carcinoma (HCAM) were treated for 72 hours using different concentrations for Cisplatin and Docetaxel. The IC50 values of docetaxel and cisplatin after 72 h exposure for HCAM was 12.82 and 10.74 respectively. Our in vitro results demonstrate that Docetaxel and Cisplatin are toxic to HCAM cell line in a concentration-dependent manner. In conclusion, our results showed positive expression of p53, EGFR, and weak HER2/neu. Also, HCAM cell line showing to be sensitive to docetaxel and cisplatin, which inhibit cell proliferation.